Aplikasi Pengelolaan Data Produksi Pada Ud. Rendy Jaya Keramba Berbasis Mobile Android - Muhammad Kusuma Prawiro; Damar Nucahyono; Farindika Metandi (CV MEDAN TEKNO SOLUSI, 2025)
The use of efficient information systems in business ventures is an important factor to improve operational progress. This research aims to develop an Android mobile-based production data management application for UD. Rendy Jaya Keramba, a fish farming business in Tenggarong, East Kalimantan. Currently, UD. Rendy Jaya Keramba still uses manual methods in managing inefficient production data. Through a system development approach using the waterfall method, the designed application will replace the manual method by focusing on production data input, data search, and production report generation. The use of this application is expected to increase the efficiency and effectiveness of data management and accelerate the decision-making process for UD. Rendy Jaya Keramba. The research methods used include observation, interviews, and literature studies. With this application, it is expected to help maintain operational stability and improve performance to UD. Rendy Jaya Keramba.